8457 A multidisciplinary QI project to aid implementation of criteria led discharge in acute medical admission unit (AMAU) in children’s health Ireland at Crumlin - Dore, Andrew; Abushanab, Raneem; Lewis, Sarah; Byrne, Jessica; Cox, Marie Ann; Dominguez, Drexie; Scanlan, Barry; Kelleher, Suzanne; Donnelly, Jean (Archives of disease in childhood, 2025)
Why did you do this work?Criteria led discharge (CLD) of patients can improve patient flow, reduce length-of-stay (LOS) and improve patient experience.1 2 CLD was launched for gastroenteritis, viral-induced wheeze, bronchiolitis and minor head injury, at two sites in Children’s Health Ireland (CHI) in June 2024. Though previously piloted, CLD has not yet been incorporated into practice in Irish paediatric hospitals.This aim of this project was to use QI methodology to support and assess the implementation of CLD of a short-stay, high-turnover paediatric admission unit.What did you do?Two Plan-Do-Study-Act (PDSA) cycles were completed during the study period from June-September 2024. Data on admissions to AMAU was collected using a paper record, to determine the suitability of patients for CLD, along with rate of uptake, and completion of CLD. The team included consultants, junior doctors, nurse managers and staff nurses.Feedback about attitudes to CLD from nursing staff was gathered using an anonymous, E-questionnaire between PDSA cycles, followed by an education session to address concerns and increase staff confidence.Other interventions included consultant and trainee education, posters prompting use of CLD, and championing by the project team. Our team attended QI training.What did you find?In the initial PDSA cycle, 24 of 67 (36%) discharges were deemed CLD-suitable, with 6 out of 24 cases (26%) having CLD initiated and completed.The following PDSA cycle showed an increase in the implementation of CLD, with 6 of 20 discharges deemed CLD suitable, and 4 of 6 cases having CLD initiated and completed. This indicated 66% compliance with CLD – an improvement.Our questionnaire was answered by 7 of 11 eligible nurses. 43% felt nervous about discharging patients, while 57% described themselves as enthusiastic. Only 29% had no major concerns, while the remainder had concerns over discharging a patient too early, receiving a complaint and inadequate training.All respondents had performed CLD and all believed that members of the MDT other than doctors should be able to discharge patients.There was a high level of confidence in CLD of gastroenteritis. Less confidence was noted in viral-induced wheeze and bronchiolitis. This was addressed by an education session.What does it mean?We’ve demonstrated that local compliance with CLD can be improved using QI methodology and multi-disciplinary collaboration, along with targeted staff education. Through the PDSA cycles, we have demonstrated an increase in utilisation of CLD during the period of our study. Our questionnaire suggests that nursing staff are keen for ongoing implementation and increased training.We believe that with ongoing awareness and education around CLD, it can become more routine in our setting, with a view to increased use across CHI.ReferencesLees L, Solihull A. Implementing nurse-led discharge. Nurs Times. 2011;107(39):18–20National Health Service. Criteria-Led Discharge. 2024. Available at: https://www.england.nhs.uk/urgent-emergency-care/improving-hospital-discharge/criteria-led-discharge/ (accessed 12th August 2024).